The Islamic Ethics in the poetry of ‘Abdullah bin al-Mubarak - Abdul Salam, Muhammad Ismail bin (Journal of Islamic and Religious Studies, 2017)
‘Abdullah bin al-Mubark was born in Marw’ one of the prime cities in Khurasan, (nowadays in the surroundings of Afghanistan and Central Asia), in the year 118 AH. In addition to his many talents, achievements and abilities, ‘Abdullah bin al-Mubarak was also gifted in literacy, particularly in the art of poetry. He held an eloquent tongue which was recognized by all who conversed with him and his language displayed the nature of someone who had been taught well. Most of the poetry which has been recorded from him is actually his advice to others, whether they were close friends or high-ranking Caliphs and Rulers. The topics spoken of concerned the common issues which had arisen in his time (e.g. matters pertaining to theology, politics, the worldview, the community etc) and as always, they contained much wisdom and hence the books of history have sealed them and recorded them. This research article discussed Biography of Abdullah ibn Al Mubarak, The Islamic Ethics in his poetry, Impact of Rhetoric on his poetry with special concentration on the four kinds i.e. citation, impact of Quranic words, Quranic pictorial and Quranic style on his poetry.